ADOPTION AND IMPACT OF MOBILE LEARNING IN MALAYSIAN HIGHER EDUCATION - Ong Hai Liaw, Jessica; Ibrahim, Nora; Novari, Rachchamawati; Singh, Inderjit; Ismail, Amnah Saayah; Fook Wen, Kwong; Abd Rahman, Rosfazila (Universitas Gunadarma, 2025)
Mobile learning has become an integral component of higher education in Malaysia, driven by advancements in technology and increased accessibility to digital resources. The objective of this study is to examine the implementation of mobile learning across different educational levels in Malaysia. This study employs a qualitative research approach, analyzing secondary sources such as previous research studies, journal articles, and reports, factors influencing mobile learning adoption. The findings highlight the significant role of the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Technology Acceptance Model (TAM) in understanding students' behavioural intentions toward mobile learning. These models provide valuable insights into the key determinants affecting mobile learning adoption, such as perceived usefulness, ease of use, and facilitating conditions. The study contributes to a deeper understanding of mobile learning implementation in Malaysia and offers recommendations for enhancing its effectiveness in higher education.